Fecal microbiota transplantation improves metabolism and gut microbiome composition in db/db mice - Zhang Pei-pei; Li Lin-lin; Han Xue; Li Qin-wei; Zhang Xu-hua; Liu Johnson J.; Wang Ye (Acta Pharmacologica Sinica, 2020)
Fecal microbiota transplantation (FMT) has become an effective strategy to treat metabolic diseases, including type 2 diabetes mellitus (T2DM). We previously reported that the intestinal microbiome had significant difference between individuals with normal glucose tolerance and T2DM in Chinese Kazak ethnic group. In this study, we investigated the effects of transplanted fecal bacteria from Kazaks with normal glucose tolerance (KNGT) in db/db mice. The mice were treated with 0.2 mL of fecal bacteria solution from KNGT daily for 10 weeks. We showed that the fecal bacteria from KNGT successfully colonized in the intestinal tract of db/db mice detected on day 14. In the FMT-treated db/db mice, the levels of fasting blood glucose, postprandial glucose, total cholesterol, triglyceride, and low-density lipoprotein–cholesterol were significantly downregulated, whereas high-density lipoprotein–cholesterol levels were upregulated. In the FMT-treated db/db mice, Desulfovibrio and Clostridium coccoides levels in gut were significantly decreased, but the fecal levels of Akkermansia muciniphila and colon histone deacetylase-3 (HDAC3) protein expression were increased. At 8 weeks, both intestinal target bacteria and HDAC3 were correlated with glycolipid levels; Akkermansia muciniphila level was positively correlated with HDAC3 protein expression (r = +0.620, P = 0.037). Our results suggest that fecal bacteria from KNGT could potentially be used to treat diabetic patients.